Duration of Second Stage of Labour at Term and Pushing Time: Risk Factors for Postpartum Haemorrhage. Issue 2 (14th February 2017) - Looft, Emelie; Simic, Marija; Ahlberg, Mia; Snowden, Jonathan M.; Cheng, Yvonne W.; Stephansson, Olof
Abstract: Background: Prolonged labour is associated with increased risk of postpartum haemorrhage (PPH), but the role of active pushing time and the relation with management during labour remains poorly understood. Methods: A population‐based cohort study from electronic medical record data in the Stockholm‐Gotland Region, Sweden. We included 57 267 primiparous women with singleton, term gestation, livebirths delivered vaginally in cephalic presentation in 2008–14. We performed multivariable Poisson regression to estimate the association between length of second stage, pushing time, and PPH (estimated blood loss >500 mL during delivery), adjusting for maternal, delivery, and fetal characteristics as potential confounders. Results: The incidence of PPH was 28.9%. The risk of PPH increased with each passing hour of second stage: compared with a second stage <1 h, the adjusted relative risk (RR) for PPH were for 1 to <2 h 1.10 (95% confidence interval (CI) 1.07, 1.14); for 2 to <3 h 1.15 (95% CI 1.10, 1.20); for 3 to <4 h 1.28 (95% CI 1.22, 1.33); and for ≥4 h 1.40 (95% CI 1.33, 1.46). PPH also increased with pushing time exceeding 30 min. Compared to pushing time between 15 and 29 min, the RR for PPH were for <15 min 0.98 (95% CI 0.94, 1.03); for 30–44 min 1.08 (95% CI 1.04, 1.12); for 45–59 min 1.11 (95% CI 1.06, 1.16); and for ≥60 min 1.20 (95% CI 1.15, 1.25). Conclusions: Increased length of second stage and pushing time during labour are both associated with increased risk of PPH.